Familial syndromes associated with neuroendocrine tumours - Gut, Paweł; Komarowska, Hanna; Czarnywojtek, Agata; Waligórska-Stachura, Joanna; Bączyk, Maciej; Ziemnicka, Katarzyna; Fischbach, Jakub; Wrotkowska, Elżbieta; Ruchała, Marek (Contemporary Oncology/Współczesna Onkologia, 2015)
Neuroendocrine tumours may be associated with familial syndromes. At least eight inherited syndromes predisposing to endocrine neoplasia have been identified. Two of these are considered to be major factors predisposing to benign and malignant endocrine tumours, designated multiple endocrine neoplasia type 1 and type 2 (MEN1 and MEN2). Five other autosomal dominant diseases show more heterogeneous clinical patterns, such as the Carney complex, hyperparathyroidism-jaw tumour syndrome, Von Hippel-Lindau syndrome (VHL), neurofibromatosis type 1 (NF1) and tuberous sclerosis. The molecular and cellular interactions underlying the development of most endocrine cells and related organs represent one of the more complex pathways not yet to be deciphered. Almost all endocrine cells are derived from the endoderm and neuroectoderm. It is suggested that within the first few weeks of human development there are complex interactions between, firstly, the major genes involved in the initiation of progenitor-cell differentiation, secondly, factors secreted by the surrounding mesenchyme, and thirdly, a series of genes controlling cell differentiation, proliferation and migration. Together these represent a formula for the harmonious development of endocrine glands and tissue.